Effect of an Ayurvedic Herbal Formulation on Male Fertility - Ganesan, L.; Nayani, M.M.D.; Shakir, M.M.M.; Susantha, R.A.R.P.; Fernando, D. M. S.; Wijesekara, G.U.S. (Proceedings of the GARI RESEARCH CONFERENCE 2016, 2016)
Attached

Male infertility is rising at an alarming rate. Ayurveda has claimed there are plants that can be used to treat male infertility, even for idiopathic cases. The objective of the study is to describe^ the effect’ of an ayurvedic herbal formulation on male infertility which consists of plantsWithaniasomnifera(Am.\ikkaxeL),Orchis mascula,Mucunapnaiens(Vttidunima), Tribulus terrestris (Heen nerenchi), Asparagus racewojas(Hathavariya), Asparagus adscendens, Anacycluspyrethrum(;Akrapatia) and Myristica _/^ag/-ans(Sadikka). = Infertile subjects (n=68) attended to Nugegoda Ayurvedic clinic were treated with herbal formulation for three months. Seminal fluid samples were collected and analyzed at baseline (pretreatment) and first, second and third months on medication: Comparisons' of the sperm concentration, total motility, progressive motility and semen volume between pretreatment and post treatment were done by paired T test The percentage of increase in sperm concentration, total motility, progressive motility and semen volume at the end of 3 month were 88.47%, 63.94%, 78.41% and 4.18% respectively. Positive correlations were found in sperm concentration (r=0.45), total motility(r=0.42) and progressive motility (r=0.53) between pretreatment and post treatment and a highly significant increase was observed in all above semen parameters (p=0.001) except semen volume following treatment for 3 months. Further, findings indicated a highly significant improvement (p=0.001) in sperm concentration, total motility and progressive motility of the treated oligozoospermic (n=54), asthenozoospermic (n=64) and oligoasthenozoospermic (n=50) groups. In conclusion, the herbal formulation has a positive effect on sperm concentration, total motility and progressive motility imoligozoospermie, asthenozoospermic and oligoasthenozoospermic:
Keywords: Infertility; Herbal formulation; Seminal fluid